PENGARUH SUDUT PEMASANGAN MINI DENTAL IMPLANT NON-PARALEL TERHADAP RETENSI GIGI TIRUAN LENGKAP OVERDENTURE RAHANG BAWAH ( PENELITIAN IN VITRO ) - , Anak Agung Istri Putri, drg. Titik Ismiyati, MS., Sp. Pros (K). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Overdenture is defined as a removable partial denture or complete denture that covers on roots of natural teeth or dental implants. Prime function of overdenture is to improve retention and stabilization of denture, particularly complete denture. The support of overdenture could be obtained from natural teeth, the roots of natural teeth, or dental implant. The retention in overdenture that using mini dental implant as their support. The aim of this study is to evaluate the effect of mini dental implant nonparallel assembly as overdenture support toward retention of complete denture at lower jaw. Sample of this study was 30 complete denture of lower jaw, which has been grouping into 3 groups : 10 dentures for assembly of MDI parallel 00, 10 dentures for assembly of MDI non-parallel 100, and 10 dentures for assembly of MDI non-parallel 150. MDI 1,8 x 18 mm IMTEC 3M was used in this study. Two MDI as male attachment was arranged at element 33 and 43 in each edentulous lower jaw model with assembly of parallel 00, non-parallel 100, and non-parallel 150 toward median line, whereas the female attachment (metal housing) was arranged on fitting surface acrylic resin of complete denture lower jaw appropriate with the implant position that has been marked with indelible pencil on the head of implant. Overdenture was arranged on modified Van Kempen instrument and tensile strength test was held then evaluated with one way Anova (Î± = 0.05). The result showed that there was significant retention strength differences between MDI assembly of non-parallel 100 with non-parallel 150 (p<0.05). The conclusion of this study is MDI assembly of non-parallel 150 has stronger retention than non-parallel 100and than parallel 0Â°.